Design and Application of Public Welfare Posters Based on 5G Wireless Network. (27th May 2022) - Xiao, Wei; Li, Xingping
Abstract : As a traditional communication medium, public welfare posters take the public welfare issues of social concern as the theme, through visual images and creative connotation to dialogue with the audience, advocate social values, and convey positive energy. Nowadays, the audience's aesthetic requirements and level of design awareness are gradually increasing; whether emerging public welfare posters can be truly accepted and achieve good communication effect depends not only on the excavation of new thematic content but also on designers' willingness to try new things in the communication environment. As the medium of public service information dissemination, public service posters also reflect the characteristics of the communication tools used in the era and have a profound impact on human production, life, cognition, and communication. In the 5G era, the rapid development of mobile communication and digital technology has injected fresh power into the change and innovation of public service posters, and the evolution of public service poster media technology has changed the communication relationship between public service information and audiences.